Strategi Pemasaran Produk IB Hijrah Haji Dalam Meningkatkan Jumlah Nasabah Pada Bank Muamalat Cabang Stabat - Budi Prianto; Nursantri Yanti (STIKes Ibnu Sina Ajibarang, 2024)
This research aims to analyze the planning, implementation, and recommendation of marketing strategies to increase the number of customers at Bank Muamalat KCP Stabat during the pandemic. The research method employed is qualitative descriptive. Data collection techniques include primary and secondary data through interviews, observation, and documentation. The research results indicate that the marketing strategy planning during the pandemic involves adding marketing channels and focusing on promotion through digitalization. The most effective strategy implemented is personal selling. Additionally, Bank Muamalat also engages in promotion through direct selling, distributing brochures, and social media. While the strategies are performing well, there are some challenges faced. Proposed solutions include adding marketing channels, offering multi-purpose Hajj financing programs, or opening Hajj savings accounts. Marketing strategy recommendations include the Bank capitalizing on existing opportunities, enhancing promotion through social media and direct outreach, and maintaining good relationships with collaborating parties.